Diffusion controlled early-stage L12-D023 transitions within Al3Zr. (1st July 2023) - Pan, Shiwei; Li, Chunan; Qian, Feng; Hao, Longlong; Li, Yanjun
Abstract: Antiphase boundary (APB) in Al3 Zr was regarded to play an important role in the L12 -D023 phase transition, the formation of which has long been explained through the shearing/slipping mechanism. Herein, the detailed atomic structures of conservative {100} APBs within L12 -Al3 Zr particles forming at the early-stage of L12 -D023 transition in an Al-Zr alloy were systematically studied by high angle annual dark-field scanning transmission electron microscope (HAADF-STEM). As a strong evidence of diffusion-limited phase transformation process, significant de-ordering of atoms in APBs and the neighboring atomic planes have been found. By analyzing the two possible pathways, it is suggested that L12 -D023 phase transition has been achieved through a diffusion mechanism, instead of shearing mechanism while the formation of APB is an intermediate stage of the phase transition process. First principles density functional theory (DFT) reveals that the formation of APBs and subsequent phase transition are energetically favorable, which provide the driving force for diffusion. Graphical abstract: Image, graphical abstract